Muhammad Asad’s Approach to Shari’ah - Showkat Ahmad Dar (Journal of Islamic Thought and Civilization, 2015)
Sharī‘ah, the sacred and revealed guidelines from the Creator, that covers of all the tenets, beliefs and laws of Islam. However, in the contemporary times what essentially constitute the “Sharī‘ah” and accordingly its implementation is complex. Some argue that it includes the laws coming forth from clear-cut injunctions of Qur’an and Sunnah while others add Ijmā and Qiyās as the sources of Sharī‘ah. Besides, limiting the establishment of Sharī‘ah merely to the implementation of some corporal punishments (literally adūd, Qiā and Ta‘zīrāt) created an Islamophobic environment and people think these laws as inhuman. On contrary Sharī‘ah is considered akin to human nature and indispensable for the peace and harmony in the world; the absence and negligence of which in practical level causes imbalance and disorder in the world. Muhammad Asad (1900-1992), a great Muslim thinker with Jewish roots tried to eradicate the misconception about the Sharī‘ah from Muslim and non-Muslim reader. He proposed that Shariah, if applied, would be helpful in minimizing the tension caused due to the presence of various schools of jurisprudence. The present study is an attempt to explore Asad’s approach and understanding of Sharī‘ah and analyze his propositions that are still valid in the contemporary period.